"How are running shoes assessed? A systematic review of characteristics and measurement tools used to describe running footwear". Issue 14 (18th July 2019) - Ramsey, Codi A.; Lamb, Peter; Kaur, Mandeep; Baxter, G. David; Ribeiro, Daniel Cury
ABSTRACT: Background : Many footwear characteristics are argued as risk factors for running related injuries (RRI). Several footwear assessment tools are available; however, their use in studies of RRI is unknown. Objective : This systematic review evaluated the characteristics and methods of assessing footwear in studies of RRI. Design : Five online databases were searched for studies on adult runners, in running style footwear, who experienced running-related pain or injury. The methodological quality of included articles was independently assessed by two raters using a modified Downs and Black checklist. Study and participant characteristics, footwear assessment tools used, and footwear characteristics reported were extracted for qualitative synthesis. Results : Twenty-four articles were included in the review. Low risk of bias was determined for 11 (44%) of the included studies. Twenty-eight different footwear characteristics were grouped into four categories: nomenclature, measurements, qualitative features, and subjective features. Fifteen different methods for assessing the 28 footwear characteristics were reported among the included studies. Only three methods were described previously, as valid and reliable. Conclusion : Differences in assessing footwear may mask the link between footwear characteristics and injury risk. Systematic footwear assessments and nomenclature are needed to evaluate the effects of footwear characteristics on RRI.